Tindak Pidana Pencabulan Anak di Wilayah Hukum Polres Boalemo Dalam Perspektif Kriminologi dan Penegakan Hukum - Yulita Liba; Lisnawati W Badu; Supriyadi A Arief (Indonesian Journal Publisher, 2026)
The purpose of this study is to analyze the high incidence of sexual violence against children in Boalemo Regency from a criminological perspective and to assess the effectiveness of law enforcement practices carried out by the police, particularly the Women and Children Protection Unit (PPA) of the Boalemo Police. This study employs an empirical method with a sociological juridical approach. Data were collected through interviews, observations, and documentation studies conducted at the PPA Unit of the Boalemo Police and were analyzed qualitatively to obtain an in-depth understanding of the causal factors and countermeasures. The results indicate that sexual violence against children is influenced by both internal and external factors. Internal factors include family-related problems such as domestic disharmony, weak parental supervision, and economic conditions, while external factors encompass an unfavorable social environment, low public legal awareness, and the influence of peer associations and media. In responding to these cases, the Boalemo Police have undertaken law enforcement efforts through preventive measures, such as legal education and socialization, as well as repressive measures in the form of taking legal action against perpetrators in accordance with prevailing laws and regulations. However, these efforts have not been fully effective, as the incidence of sexual violence against children remains relatively high and tends to increase annually. Therefore, it can be concluded that strengthening more comprehensive and sustainable law enforcement strategies is necessary, along with enhancing the role of families, communities, and local government in efforts to prevent and protect children.